Village-Based Institutional Development Strategy to Prevent the Paddy-Field Conversion at Pandeglang Regency, Banten, Indonesia - Koesmaryono, Yonny; Kolopaking, Lala M. (European Journal of Economics and Business Studies, 2017)
Indonesia government needs innovative policies preventing the paddy-field conversion in the current era of regional decentralization. Average of paddy-field conversion in Indonesia has reached 187,200 hectares per year. Irrigated-paddy-field in Indonesia that converted to non-agricultural purpose in 2009 had already reached 3.09 million hectares (42.4 percent). The highest conversion areas were in Java and Bali islands that reached 1.67 million hectares. The study in Pandeglang Regency has shown the prior strategy to prevent paddy-field conversion. It requires the integration the protection toward the peasant based on inter- village participatory partnership to develop the rural area. The developed institution should follow the current applicable regulation, namely the Local Public Service Agency or Badan Layanan Umum Daerah (BLUD) to protect the paddy-fields. It does not only by managing logistic to support the production of the peasants, but also as a synchronizer among multi-parties for the empowerment actions of the peasants to manage the paddy-field farming. The government should use various development approach policies to prevent paddy-field conversion. Top-down development and bottom-up approach is required to be affirmed. Moreover, technocratic approach should be supported by participatory development. Otherwise, the stakeholders should be involved to implement the rural-based institutional development strategy preventing the paddy-field conversion.